Persepsi masyarakat terhadap asuransi syariah - Tati Handayani; Muhammad Anwar Fathoni (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
Islamic insurance is one of the option that can be choosen by Muslim society, because it offers a way of investing to prevent future risks. The success of Islamic insurance companies cannot be separated by community participation in insurance business. This research is aimed to examine and analyze public perception on the existance of Islamic insurance. A descriptive quantitative analysis is used as the research method. This research set Jabodetabek people as the population and sample by using convenience sampling technique. The results show that premium and promotion do not effectively affect public perception, therefore, insurance company must do more socialization about Islamic insurance to Muslim communities.